The View Outside of the Box: Reporting Outcomes Following Radical Cystectomy Using Pentafecta From a Multicenter Retrospective Analysis - Zapała, Łukasz; Ślusarczyk, Aleksander; Korczak, Bartłomiej; Kurzyna, Paweł; Leki, Mikołaj; Lipiński, Piotr; Miłow, Jerzy; Niemczyk, Michał; Pocheć, Kamil; Późniak, Michał; Przudzik, Maciej; Suchojad, Tomasz; et al. (Frontiers in Oncology, 2022)
We aimed at characterization of the patients undergoing radical cystectomy (RC) using the prognostic model (a modified pentafecta). In the multicenter retrospective study, we enrolled 304 patients with bladder cancer (pTis-4N0-2M0), who underwent RC between 2015-2020 in experienced centers. The definition of the pentafecta was as follows: no Clavien-Dindo grade III-V complications at 90 days and no long-term complications related to urinary diversion <12 months, negative surgical margins, ≥10 lymph nodes (LNs) resected, and no recurrence ≤12 months. RC-pentafecta achievement rate was 22% (n=67), varying from 47 to 88% attainment rate for different pentafecta components and was lowest for sufficient LNs yield. Both 12-month recurrence-free survival (RFS) and cancer-specific mortality were compromised in pentafecta failers compared to achievers (57.8% vs. 100% and 33.8% vs 1.5%, respectively). The followings were identified as crucial predictors of RC pentafecta achievement: modality of the surgery, type of urinary diversion, histological type of bladder cancer, advanced staging and elevated preoperative serum creatinine. In conclusions, we found that the pentafecta achievement rate was low even in high volume centers in patients undergoing cystectomy. The complexity of the procedure directly influenced the attainment rate, which in turn lead to increase in cancer-specific mortality rate among the pentafecta failers.